Influence of processing route on electrical properties of Bi4Ti3O12 ceramics obtained by tape-casting technology - Ranieri, M. G.A. [UNESP]; Aguiar, E. C. [UNESP]; Cilense, M. [UNESP]; Stojanovic, B. D.; Simões, A. Z. [UNESP]; Varela, J. A. [UNESP] (Elsevier, 2015)
Bismuth titanate powders (Bi4Ti3O12-BIT) were fabricated by solid state reaction (SSR) and polymeric precursor method (PPM). From these powders, Bi4Ti3O12 pellets were obtained by tape-casting using plate-like templates particles prepared by a molten salt method. The BIT phase crystallizes in an orthorhombic structure type with space group Fmmm. Agglomeration of the particles, which affects the densification of the ceramic, electrical conduction and leakage current at high electric fields, was monitored by transmission electronic microscopy (TEM) analyses. FEG-SEM indicated that different shape of grains of BIT ceramics was influenced by the processing route. Both SSR and PPM methods lead to unsaturated P-E loops of BIT ceramics originating from the highly c-axis orientation and high conductivity which was affected by charge carriers flowing normally to the grain boundary of the crystal lattice.
Keywords: A. Ceramics; B. Chemical synthesis; C. X-ray diffraction